Kinetic simulation of uranium migration in granite fissure media of beishan, gansu, China: A case study based on the Laplace transform and inverse transform methods - Xianzhe Duan; Cong Du; Nan Li; Jiaxin Duan; Zhenping Tang (Nuclear Engineering and Technology)
Deep geological disposal is currently considered the most practical and feasible method for disposing high-level radioactive wastes (HLWs). One of its key scientific issues is the migration of nuclides in fissure media. However, studies on the migration of nuclides like U-238 are relatively limited. In this study, the granite rock masses in Beishan, Gansu were selected to construct a physical and mathematical model of U-238 migration using the Laplace transform and inverse transform methods. Based on the numerical methods, the kinetic migration of nuclide U-238 in the fissure media of granite was simulated, and the effects of parameters such as fissure width, hydraulic gradient, diffusible area ratio and rock porosity on the migration of U-238 were investigated. The following insights were obtained: (1) After 100,000 years, U-238 has a very limited diffusion depth in the matrix domain, with a diffusion range of only a few tens of millimeters, whereas it migrates relatively quickly in the fissure domain, with a maximum migration distance of about 1500 m. (2) Under the same migration time and distance, the relative concentration of nuclide U-238 in the fissure domain increases with larger gap width, hydraulic gradient, and diffusible area ratio, but decreases with higher rock porosity. (3) In the same time range, the rock masses with larger gap widths, hydraulic gradients, and diffusible area ratios have larger migration ranges, while those with higher porosities have smaller migration ranges. (4) While selecting a site for diposal of HLWs, it is recommended to choose rock masses in the granite area of Beishan with no fissures or few fissures; additionally, areas with smaller fissure widths, hydraulic gradients, and diffusible area ratios but higher rock porosity should be prioritized. This study can provide important theoretical support for understanding nuclide migration in the future geological disposal of HLWs.